Clinical-Biological Correlations of Chronic Respiratory Diseases and Oro-Dental System - Dragos Munteanu; LI Pertea; A Vlase*; R Ciorap; MI Ungureanu; CT Oniciuc (Global Journal of Medical and Clinical Case Reports, 2025)
Abstract One of the most common chronic respiratory diseases, incapacitating the development and quality of life of patients and directly correlated with the oro-dental cavity is represented by asthma or Chronic Obstructive Pulmonary Disease (COPD), a chronic inflammatory disease affecting the airways, in which mast cells, eosinophils, and T lymphocytes, play an important role. A better understanding of the diagnosis and treatment of asthma became possible by accepting that the existence of chronic inflammation, with its variations, is reflected in the clinical condition of the patient, with implications on the dental status. Scope of the study: Determination of the prevalence and severity of oro-dental pathology in patients with chronic respiratory diseases, respectively clinical and biological correlations, namely of individualized regimens, according to associated comorbidities that would contribute to improving the quality of life. Materials and method: A study was conducted on a group of 167 patients hospitalized in the Internal Medicine Clinic, for one year (2021-2022) and also on 53 patients consulted in a dental ambulatory unit. Results and discussion: The investigations showed an increased prevalence of gingivitis, chronic marginal superficial periodontitis, and coated tongue, possibly caused by insufficient ventilation in the nose or pulmonary obstructive diseases and mouth breathing predominance. Angular cheilitis and stomatitis have been also had in view, as diseases of the oral cavity, in patients with asthma and Chronically Obstructive Pulmonary Diseases (COPD). Such cases were more frequent in male than in female patients, a possible explanation being the higher prevalence of smoking and increased exposure to professional allergens for males, as well as a higher incidence of viral and / or bacterial superinfections. Conclusion: The study carried out highlighted over 41.1% of the patients with chronic respiratory diseases and COPD/bronchial asthma (AB) presented angular cheilitis (11.6% cases), stomatitis (22.3% cases) and candidiasis (11.2% cases). In the experimental group, the level of oral hygiene is more satisfactory in women than in men, the same proportion being preserved in smoking and nonsmoking patients. Also, caries occurs more frequently in men than in women, the causes being, once again, health education, oral hygiene status and smoking.